Pencegahan Stunting Masyarakat Digital Di Kelurahan Sukomoro, Kecamatan Talang Kelapa, Banyuasin - Ardiansyah; Dita Mayreista; Trecy Austin; Nopriawan Mahriadi (CV. Multi Kreasi Media, 2023)
This community service aims to describe and discuss the efforts made by the government and the digital community to overcome the problem of stunting in Sukomoro Village, Talang Kelapa District, Banyuasin Regency. This service uses a socialization or counseling method involving 45 participants, including the people of Sukomoro Village, Talang Kelapa District, Banyuasin Regency. Meanwhile, the data sources used consist of primary and secondary data. Partners in this service are the Village Midwife in Sukomoro sub-district, sub-district head, health authorities, religious shops and the community. The findings show that the government has made efforts to overcome the stunting problem in the Sukomoro sub-district, but there is minimal outreach regarding the stunting problem. Solving the problem of lack of understanding and public awareness regarding the prevention and handling of stunting in babies and toddlers under the age of 2 years, which can be prevented through information that can be obtained from the internet on a digitalization basis. In order to empower and also increase public awareness of the importance of stunting, it is estimated that the public will be more willing to follow this digitalization trend.